RELASI KREDIBILITAS DA’I DAN KEBUTUHAN MAD’U DALAM MENCAPAI TUJUAN DAKWAH - Hariyanto Hariyanto (TASÂMUH, 2018)
Da'wah orientation is not centered on the interests of da'I, but the need of mad'u. Mad'u has diverse expectations of da'i ranging from the selection of da'wah methods, material submitted and media used. It thus requires da'i to have internal and external provisions. Internal provision can be the ability to communicate, self-control, and knowledge. The external provision refers to the ability of da'i to read the psychological condition of mad'u and the environment of da'wah. Thus, da'i can determine a wise, empathetic, sympathetic and humanist approach of da'wah. In the principle of communication is known by the rules of dependency relationship. On the one hand da'i has the right to speak and on the other hand mad'u has the right to hear. The right to talk da'i must be accompanied by the obligation to listen to mad'u and the right to hear mad'u should be accompanied by the appreciation of the message of da'i preaching. This study will explore relation credibility of da’i and mad’u needs into reach goal of dakwa descriptive with the "tools" analysis of Jude Burgoon Theory.